已知A=-3m^3-3/5m^2+m-1,B=1/2(-6m^3+4/5m^2-2m)+3,求5A-3B-【-A-(2B-5A)】
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 09:20:08
已知A=-3m^3-3/5m^2+m-1,B=1/2(-6m^3+4/5m^2-2m)+3,求5A-3B-【-A-(2B-5A)】已知A=-3m^3-3/5m^2+m-1,B=1/2(-6m^3+4/
已知A=-3m^3-3/5m^2+m-1,B=1/2(-6m^3+4/5m^2-2m)+3,求5A-3B-【-A-(2B-5A)】
已知A=-3m^3-3/5m^2+m-1,B=1/2(-6m^3+4/5m^2-2m)+3,求5A-3B-【-A-(2B-5A)】
已知A=-3m^3-3/5m^2+m-1,B=1/2(-6m^3+4/5m^2-2m)+3,求5A-3B-【-A-(2B-5A)】
5A-3B-[-A-(2B-5A)]=5A-3B+A+2B-5A=A-B
=-3m³-3/5m²+m-1-[(-3m³+2/5m²-m)+3]
=-3m³-3m²/5+m-1+3m³-2m²/5+m-3
=-m²+2m-4
已知m^2-5m+1=0,求m^3+1/m^3 和m-1/m的值
已知m>4,化简|m-4|+|7-2m|+|m×m-2m+1|-|m×m-2m-3|
已知2^m=a,化简16×2^2m-1 ×2^3m-1 -4^m ×8^m
已知2^m=a,化简16×2^2m-1 ×2^3m-1 -4^m ×8^m
已知a^3*a^m*a^2m+1=a^25,求m的值
(m+3m+5m+...+2015m)-(2m+4m+6m+...+2014m)=
m-2m-3m+4m-5m-6m+7m.2004m=?
(m+3m+5m.+2013m)-(2m+4m+6m+.+2012m)=?
已知m^2+m-1=0,那么m^4+2m^3-m-2009=
已知m·m+m-1=0,则m^3+2m^2+2004=?
已知m+1/m=3,计算(m^4+m^2+1)/m^2的值
已知m²+2m+1=0,求m³+2m²+3m
已知3/m-5+A/5-m=3,那么A等于 A.m-8 B.2-m C.18-3m D.3m-12
已知m-1/m=3,m不等于0,求m^2-1/m^2,m^3-1/m^3,m^4-1/m^4
已知m^2+m-1=0,求代数式m^3+5m^2+3m-2012的值
已知m^2+m-1=0,求m^3+5m^2+3m-2009的值.
已知m^2-5m-1=0,求3m^2-10m+1/m^2
已知m^a=3,m^b=5,m>0且a+b=2,求m的值